2022
DOI: 10.1042/cs20210506
|View full text |Cite
|
Sign up to set email alerts
|

Targeting skeletal muscle mitochondrial health in obesity

Abstract: Metabolic demands of skeletal muscle are substantial and are characterized normally as highly flexible and with a large dynamic range. Skeletal muscle composition (e.g., fiber type and mitochondrial content) and metabolism (e.g., capacity to switch between fatty acid and glucose substrates) are altered in obesity, with some changes proceeding and some following the development of the disease. Nonetheless, there are marked interindividual differences in skeletal muscle composition and metabolism in obesity, som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 385 publications
0
4
0
Order By: Relevance
“…While it is not clear whether the alteration in fiber type distribution in the muscle of obese individuals is a cause or a consequence of obesity [ 11 ], recent studies with human models have reported a reduction of type I fibers in obese individuals. This phenomenon is linked to the metabolic environment associated with obesity, particularly concerning the content and function of mitochondria [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is not clear whether the alteration in fiber type distribution in the muscle of obese individuals is a cause or a consequence of obesity [ 11 ], recent studies with human models have reported a reduction of type I fibers in obese individuals. This phenomenon is linked to the metabolic environment associated with obesity, particularly concerning the content and function of mitochondria [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, reduced activity of citrate synthase, an important enzyme in the mitochondrial energy system, has been reported in subjects affected by obesity and insulin resistance [ 9 ]. Considering the impact of mitochondrial content in oxidative muscle fibers, alterations of the mitochondrial systems have been identified as a factor contributing to the loss of type I fibers in obese individuals [ 10 , 11 , 12 ]. However, whether the alteration in muscle fiber composition is a cause or consequence of obesity remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PGC-1 α overexpression ameliorates angiotensin II-induced hypertension via the regulation of eNOS [ 41 ]. SDH is one of the molecules that are stimulated by PGC-1 α and is an essential component in both the citric acid cycle and the electron transport system in mitochondria, and the elevations of the mitochondrial fraction and oxidative phosphorylation in skeletal muscle are intimately correlated with weight loss [ 42 , 43 ]. In this study, buspirone increased the protein levels of PPAR δ , AMPK, and PGC-1 α in skeletal muscle and abdominal fat tissues from SHRs and elevated the SDH activity in the skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that an inability to adapt to metabolic stimuli, such as insulin signaling or fatty acid exposure, may lead to the decrease in muscle oxidative capacity characteristic of obesity [ 67 , 68 , 69 ]. In their study including 28 juvenile Iberian pigs fed either a control or a high-fructose, high-fat (HFF) diet for 10 weeks, H.C. Spooner et al [ 70 ] demonstrated that the HFF diet resulted in decreased IMCL fat content and in the formation of less oxidative skeletal muscle phenotype, reflecting the disturbed ability of skeletal muscles to use lipids as a fuel.…”
Section: Skeletal Muscles In Obesitymentioning
confidence: 99%